Art journey New Mexico : 104 painters' perspectives (Cincinnati, Ohio Collector's Guide, 2009)
Nothing compares to the creative spirit found throughout this inspiring land and the artists who inhabit it. Art Journey New Mexico communicates the stunning vistas, distinctive architecture and sparkling light only found here. This dynamic showcase of the work of 104 of New Mexico's top gallery artists takes you on a trip inside their world by presenting personal favorites and major pieces in this beautiful book. Discover the insights, techniques and inspiration of these artists, as well as how their work expresses their creative spark. The art is diverse, covering a variety of mediums, subjects and styles ranging from Native American and Spanish Colonial traditions to cutting-edge, modern interpretations. AbeBooks.com
Includes index
100071
Keywords: Painting, American -- New Mexico -- 21st century